FAKTOR – FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS (Studi pada beberapa Badan Usaha Milik Negara di Indonesia) - Dwi Suci Annisa Yosandra; Ferikawita M Sembiring (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
The purpose of this research was to determine the effect of debt to equity ratio, fixed asset ratio, net profit margin, current ratio, and firm size on financial distress (Springate score) partially and simultaneously. This research uses secondary data, namely State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample of this research is 13 companies, with the method used is non-probability sampling with purposive sampling technique. The data analysis used is panel data regression analysis using software Eviews 12. The fixed effect model was selected through 2 tests of panel data regression model tests. The results of this research indicate that: (i) the fixed asset ratio has an effect positive effect on financial distress, (ii) net profit margin has a negative effect on financial distress, (iii) current ratio has a negative effect on financial distress. There are 2 independent variables that have no effect, including: (i) debt to equity ratio and (ii) firm size. All variables simultaneously affect financial distress.